2000
DOI: 10.1088/0957-4484/11/4/327
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric figure of merit enhancement in a quantum dot superlattice

Abstract: We theoretically investigated electron and phonon transport in a quantum superlattice and evaluated a possible thermoelectric figure of merit increase. The presented model takes into account electron and phonon transport modifications due to the space confinement caused by the mismatch in electronic and thermal properties between dot and host materials. The numerical calculations were carried out for a structure that consists of multiple layers of Si with regimented quantum dots separated by wetting layers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 13 publications
1
47
0
Order By: Relevance
“…The optimum distribution occurs when the size range of the inclusions is approximately equal to the wavelength range of the dominant heat-carrying phonons, which in many semiconducting thermoelectric materials falls roughly in the 2 to 100 nm range. [26,27] Our investigations during this study of the Ag 0.53 Pb 18 Sb 1.2 Te 20 system have shown that these conditions are approached in many of the samples studied, rationalizing the low thermal conductivity and high figure of merit observed in these alloys. Based on our TEM results, we find an average of 28 cylindrical inclusions within a volume of 110 Â 110 Â 25 nm 3 ; each possessing a diameter of 5 nm and a thickness of 1 nm.…”
Section: Resultsmentioning
confidence: 55%
“…The optimum distribution occurs when the size range of the inclusions is approximately equal to the wavelength range of the dominant heat-carrying phonons, which in many semiconducting thermoelectric materials falls roughly in the 2 to 100 nm range. [26,27] Our investigations during this study of the Ag 0.53 Pb 18 Sb 1.2 Te 20 system have shown that these conditions are approached in many of the samples studied, rationalizing the low thermal conductivity and high figure of merit observed in these alloys. Based on our TEM results, we find an average of 28 cylindrical inclusions within a volume of 110 Â 110 Â 25 nm 3 ; each possessing a diameter of 5 nm and a thickness of 1 nm.…”
Section: Resultsmentioning
confidence: 55%
“…56 Prasher 57,58 has had considerable success obtaining analytical solutions to the Boltzmann equation for simple geometries. Scattering models based on Rayleigh scattering 59 and acoustic Mie scattering theory 60 have also been used to treat nanoparticle scattering. Minnich and For the present work we use a standard boundary scattering rate.…”
Section: A Phonon Scatteringmentioning
confidence: 99%
“…[26] The results described herein are in agreement with long-standing theoretical predictions that nanostructuring in semiconductors would lead to enhanced thermoelectric figures of merit. [25,27] The Na 1Àx Pb m Sb y Te m+2 materials could find applications in devices for power generation from a wide variety of hot sources, for example, vehicle exhausts, coal-burning installations, or electric power utilities. Na 1Àx Pb m Sb y Te m+2 (y 1) samples (see Supporting Information for synthesis details [28] ) exhibit p-type conduction from 300 to 700 K. Ingots with the composition Na 0.95 Pb 19 SbTe 21 (m = 19, x = 0.05, y = 1) exhibit an electrical conductivity of s = 1422 S cm À1 with a positive thermopower of S = 105 mV K À1 at room temperature.…”
Section: +mentioning
confidence: 99%